Optimization of Tomato Fruit Extract Gel (Solanum lycopersicum L.) Using the Simplex Lattice Design Method and Antioxidant Activity Evaluation - Salma uswatun khasanah; Anna Fitriawati; Bangkit Riska Permata (Jurnal FARMASIMED (JFM), 2026)
Background: Exposure to ultraviolet radiation and free radicals can induce oxidative stress, leading to skin damage and premature aging. Therefore, topical formulations containing effective and safe antioxidants are required. Tomato fruit (Solanum lycopersicum  L.) is known to contain flavonoids and lycopene, which act as natural antioxidants and possess potential photoprotective properties. Gel formulations were selected due to their good spreadability, cooling sensation, non-comedogenic nature, and ease of application. To achieve optimal physical quality of gel preparations, optimization of the gel base composition is necessary. Objective: This study aimed to determine the optimum formulation of tomato fruit extract (Solanum lycopersicum  L.) gel with varying concentrations of HPMC and propylene glycol using the Simplex Lattice Design (SLD) method, as well as to evaluate the physical characteristics and antioxidant activity of the resulting optimum formulation. Tomato fruit extract was obtained by maceration using 96% ethanol as the solvent. Methods: Gel formulation optimization was performed using the Simplex Lattice Design method with Design- Expert® software, involving combinations of HPMC as a gelling agent and propylene glycol as a humectant. The evaluated physical quality parameters included organoleptic properties, homogeneity, pH, spreadability, adhesiveness, and viscosity. The optimum formulation was subsequently tested for antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method by UV–Vis spectrophotometry and expressed as the IC₅₀ value. Results: The results indicated that variations in HPMC and propylene glycol concentrations significantly affected the physical characteristics of the gel formulation. The obtained optimum formulation met all the requirements for good and stable gel physical quality. Conclusion: Antioxidant activity testing demonstrated that the optimum formulation exhibited strong antioxidant activity, with an IC₅₀ value of 74.12 ppm, indicating its potential for development as a natural antioxidant topical gel.